THE ANALYSIS OF FINANCIAL LITERACY ON INVESTMENT DECISIONS AMONG WOMEN WORKING IN THE FORMAL SECTOR IN SURABAYA: THE ROLE OF FINANCIAL BEHAVIOR AND RISK TOLERANCE AS MEDIATOR - Margono, Rizky Fernanda; Anwar, Muhadjir (Yayasan Education and Social Center, 2024)
Investment is one of the many financial decisions individuals make and becomes a means of fulfilling unlimited human needs with limited resources. This research aims to determine the influence of financial literacy on investment decisions with financial behavior and risk tolerance as mediating variables on women who work in the formal sector in Surabaya City. The sample in this research is 160 respondents using a purposive sampling technique, the data collection method uses a questionnaire, and the analysis uses PLS. The research results show that financial literacy positively affects the investment decisions of women who work in the formal sector in Surabaya City. Financial behavior positively mediates the relationship between financial literacy and investment decisions of women who work in the formal sector in Surabaya City. Risk tolerance cannot mediate the relationship between financial literacy and investment decisions of women who work in the formal sector in Surabaya City